Plant-Derived Nanovesicles: A Novel Form of Nanomedicine - Yu, Lanlan; Deng, Zhun; Liu, Lei; Zhang, Wenbo; Wang, Chenxuan (Frontiers in Bioengineering and Biotechnology, 2020)
The nanovesicles extracted from the plant and herbal decoctions are identified as a new class of nanomedicine. They are involved in interspecies chemical communication across the plant and animal kingdoms and display a therapeutic potential against a variety of diseases. Herein, we review the recent progress made in the medical applications of plant-derived nanovesicles in the aspects of anti-inflammation, anti-cancer, tissue regeneration, and modulating commensal microbiota. We further summarize the cellular and molecular mechanisms underlying the physiological functions of plant-derived nanovesicles. Overall, plant-derived nanovesicles provide an alternative to conventional synthetic drugs and present exciting opportunities for future research on disease therapy.